ANALISIS LIKUIDITAS PROFITABILITAS DAN AKTIVITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN PT. SARANA AGRO NUSANTAR MEDAN PERIODE 2015-2019 - Rani Simbolon; Hotlan Butarbutar; Jon Henri Purba (Jurnal Ilmu Manajemen METHONOMIX, 2022)
This study aims to analyze the ratio of liquidity, profitability, and activity for the assessment of financial performance at PT. Sarana Argo Nusantara (Persero) for the period 2015-2019. The ratios used in this study are current ratio, cash ratio, Total Own Capital (TMS) to Total Assets (TA), collection period, inventory turnover, total asset turnover (TATO), and return on assets (ROA) and return on equity ( ROE). The data analysis method used is descriptive qualitative. The results of the research are based on the analysis of liquidity ratios, through current ratios and cash ratios, the company's financial performance is liquid, based on the ratio of Total Own Capital to Total Assets or known as TMS to TA, it can be seen that the financial performance is good, the activity ratio, it can be called the financial performance of this company. From the point of view of accounts receivable turnover ratio, inventory turnover ratio, and total asset turnover ratio are good. and the ratio of profitability as measured by return on assets (ROA) and return on equity (ROE) can be said to be good, so it can be concluded that the financial performance of PT. Sarana Agro Nusantara (Persero), 2015-2019 is healthy with the AAA category